A metal and alloy based mechanism dimensional synthesis of 8-bar planar kinematic linkage for motion generation. (2021) - Nafees, Khalid
Abstract: In this research, a computer aided design approach is applied on 8-bar; 1-DOF metal and alloy based mechanism to augment accuracy and precision requirement of automation industry. The objective is development of desired mechanism and determination of its dimensional parameters with their orientations to generate prescribed motion. The prescribed motion is defined by displaced positions of coupler orientations on the basis of input crank link rotation. For each displaced position, various analytical dyad/triad equations are generated by considering corresponding independent vector loops. To determine solution of these equations, a MATLAB program is written. The design methodology is demonstrated and verified for numerical example. Finally, all design dimensions are graphically plotted and presented in results. The proposed methodology is simple, easy to apply and yields dimensions for developing the mechanism with high accuracy and precision.